Comparison of toxicity after IMRT and 3D-conformal radiotherapy for patients with pancreatic cancer – A systematic review. Issue 1 (January 2015) - Bittner, Martin-Immanuel; Grosu, Anca-Ligia; Brunner, Thomas B.
Summary: IMRT has been suggested to reduce treatment-related toxicity in pancreatic cancer. We attempted to identify all IMRT-studies indexed in PubMed/Medline, comparing them with recent 3D-CRT trials. The predominant treatment-related toxicities, namely nausea/vomiting, diarrhoea and late GI toxicity, are significantly reduced with IMRT while there was no apparent difference for outcome measures.